Immunotherapy, checkpoint inhibitor advance to frontline non-small cell lung cancer - Nemunaitis, John; Senzer, Neil (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
For many years, immune-based therapies have been explored in a selected array of cancers traditionally considered “immunogenic”, namely melanoma, prostate, renal cell, non-Hodgkin’s lymphoma, bladder cancer, and renal cell carcinoma. Until recently, lung cancer has not been considered part of this group. Indeed, the designation “immunogenic” has essentially been ex post facto descriptive. However, our increased understanding of dynamic molecular immunology, including the multifarious immune editing process, and an expanded array of technologic tools now allow for a mechanistic classification with regard to immunogenicity.